Surface absorption illumination in a 2D thermoelastic semi-infinite medium under modified Green and Lindsay model - Ismail M. Tayel (Elsevier, 2022)
In this study, the modified Green and Lindsay model is utilized to discuss the effects of heating caused by surface absorption of laser radiation in a two-dimensional thermoelastic half-space. The temporal profile of the pulsed laser is taken as a non-Gaussian and the spatial one is a Gaussian. The medium surface is taken to be traction free. The integral transform method is utilized to obtain the general solution by applying the two transformations Hankel and Laplace, in which the inverse of Laplace is performed numerically. The Silicon material is considered as an example to verify the consistency of the obtained results of the new model.